Literature Review Konseling Multibudaya: Teknik Konseling Individu Yang Responsif Terhadap Keberagaman Budaya - A'yun, Siti Qurotul; Habsy, Bakhrudin All; Khusumadewi, Ari (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
Everyone always tries to achieve a prosperous life, through fulfilling their needs, whether biological, psychological, social, or spiritual. If in the process they encounter obstacles or failures, then the individual will experience feelings of discomfort, frustration, or even depression. In this condition, the individual needs the help of a counselor to help him return his position to a comfortable situation. As humans who grow and develop in different environments and at different times, of course there are cultural differences between counselors and clients. The relationship between counselors and clients in a humanitarian situation, which means that both counselors and clients are humans with their own characteristics, both personality, values, morals, and culture that they bring, is called multicultural counseling. Counseling techniques must also be adjusted to the situation and conditions faced while still paying attention to the cultural values ​​that apply to the counselor and client.